Aplikasi Customer Service Commitment dalam Menjaga Loyalitas Konsumen Starbucks Signing Store - Salsabila, Salsabila; Winduwati, Septia (Prologia, 2024)
Maintaining product quality, providing good service and meeting consumer expectations is the key for Food and Beverage industry activists to maintain consumer loyalty. This research aims to identify the application of Customer Service Commitment in maintaining consumer loyalty at the Starbucks Signing Store. The method used is a qualitative descriptive approach through in-depth interviews. Based on research results, Starbucks Signing Store uses the concept of Customer Relationship Management to get closer to consumers in order to create two-way communication and both Starbucks and its consumers get information which will later become material for evaluating a marketing program in Marketing Public Relations which is specifically aimed at forming a positive image of a company. brand in the long term, namely Customer Service Commitment. By implementing the Customer Service Commitment program, Starbucks Signing Store has never received negative reviews from consumers, has become a store that consistently conveys positive messages to consumers, and most importantly can retain consumers from before this store was renovated and changed the concept from a regular Starbucks to a Starbucks Signing Store. Mempertahankan kualitas produk, memberikan pelayanan yang baik dan sesuai ekspektasi konsumen adalah kunci bagi pegiat industri Food and Beverage untuk mempertahankan sebuah loyalitas dari konsumen. Penelitian ini bertujuan untuk mengidentifikasi penerapan Customer Service Commitment dalam memelihara loyalitas konsumen Starbucks Signing Store. Metode yang digunakan adalah pendekatan deskriptif kualitatif melalui wawancara mendalam. Berdasarkan hasil penelitian Starbucks Signing Store menggunakan konsep Customer Relationship Management untuk mendekatkan diri kepada konsumen agar terciptanya komunikasi dua arah dan baik Starbucks maupun konsumennya mendapatkan informasi yang nantinya akan menjadi sebuah bahan evaluasi sebuah program pemasaran dalam Marketing Public Relation yang khusus ditujukan untuk membentuk citra positif sebuah brand dalam jangka waktu panjang, yaitu Customer Service Commitment. Program Customer Service Commitment, Starbucks Signing Store tidak pernah mendapatkan ulasan negatif dari konsumen, menjadi toko yang konsisten menyampaikan pesan positif untuk konsumen, dan yang terpenting dapat mempertahankan konsumen dari sebelum toko ini direnovasi dan berubah konsep dari Starbucks biasa menjadi Starbucks Signing Store.